2021
DOI: 10.1039/d0cc08053e
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in protein metalation: structural studies

Abstract: Recent advances in structural studies unveiling the basis of the metal compounds/protein recognition process are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 110 publications
0
38
0
Order By: Relevance
“…The presence of the V center has been confirmed by inspection of the anomalous difference electron density map (Figure S13). Interestingly, although RNase A has been used as a model system in several metalation studies, Glu111 was never identified as a metal binding site. This result depends both on the accessibility of the Glu111 residue and on its affinity for the “hard” V IV ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the V center has been confirmed by inspection of the anomalous difference electron density map (Figure S13). Interestingly, although RNase A has been used as a model system in several metalation studies, Glu111 was never identified as a metal binding site. This result depends both on the accessibility of the Glu111 residue and on its affinity for the “hard” V IV ion.…”
Section: Resultsmentioning
confidence: 99%
“… 36 It has been recently pointed out that several therapies based on small molecules or oligonucleotides present the general aim of targeting RNA biology. 37 RNase A has been also frequently used as a model protein in metalation studies, and structures with several metallodrugs, 38 , 39 including cisplatin, carboplatin, oxaliplatin, 40 and Ru-, 41 Rh-, 42 Pd-, 43 Ir-, 44 and Au-based drugs, 45 are known. Recently, the metalation of arsenoplatin-1, a dual pharmacophore anticancer agent, has been presented.…”
Section: Introductionmentioning
confidence: 99%
“…MS and crystallography studies indicate that methionine, cysteine, aspartate and histidine side chains in small proteins preferentially targeted by cisplatin [ 44 – 47 ]. Crystallographic studies of cisplatin-treated nucleosomes reveal pronounced platination of solvent-exposed methionine residues [ 19 , 21 ], suggesting they are the primary sites of adduct formation in P 2 and a recent crystallographic study shows that cisplatin-protein adducts retain a certain degree of flexibility and reactivity [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic studies of cisplatin-treated nucleosomes reveal pronounced platination of solvent-exposed methionine residues [19,21], suggesting they are the primary sites of adduct formation in P 2 and a recent crystallographic study shows that cisplatin-protein adducts retain a certain degree of flexibility and reactivity [48].…”
Section: 'End 52%mentioning
confidence: 95%
“…For these reasons, alternative metallodrugs based on non-Pt metals have been synthetized, characterized and tested for biological activity in recent years [ 3 , 4 , 5 ]. Although, initially, DNA seemed the exclusive target for metallodrugs [ 6 ], successive studies have revealed that various metabolites, peptides and proteins have a central role in the recognition, transport and mechanism of action of these compounds [ 7 , 8 , 9 ]. Thus, a deeper understanding of the molecular bases of the interaction of metallodrugs with these molecules is needed.…”
mentioning
confidence: 99%